The proliferation of hematopoietic stem cells from umbilical cord blood was enhanced by using peptide sl-13r - Tien, Vu Thi; Thanh, Tran Trung; Kien, Tran Trung; An, Dinh Ho Thao; Nam, Nguyen Trung (Vietnam Journal of Biotechnology, 2024)
Umbilical cord hematopoietic stem cells (UC-HSCs) are capable of self-regeneration and differentiation into many different types of blood cells, helping to treat blood diseases such as leukemia, Hodgkin's disease and non-Hodgkin's lymphoma, as well as for transplantation. However, the number of UC-HSCs is still very small due to limitations in isolation and proliferation. In this study, UC-HSCs were cultured with the bioactive SL-13R peptide to examine whether SL-13R enhances UC-HSC proliferation. Here, we showed that CD34+UC-HSCs can be enriched by up to 47.08% by culturing total mononuclear cells (MNCs) from umbilical cord blood (UCB) in serum-free StemMACS medium supplemented with a cytokine cocktail. We demonstrated that SL-13R enhanced the proliferation of CD34+UC-HSCs by 1.21-1.44 times compared to that of the controls. These results suggested that StemMACS medium supplemented with cytokines and SL-13R can be used to expand CD34+UC-HSCs ex vivo for medical treatment and transplantation.